2014
DOI: 10.1007/s00062-014-0330-6
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm Recurrence Volumetry Is More Sensitive than Visual Evaluation of Aneurysm Recurrences

Abstract: Aneurysm recurrences were detected more frequently by aneurysm recurrence volumetry when compared with visual assessment. By using aneurysm recurrence volumetry, differences between treatment groups were detected with higher sensitivity and inter-observer validity probably because of the higher detection rate of recurrences in small aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Understanding the influence of hemodynamic forces on aneurysm initiation, growth, rupture, and recurrence after treatment can help to improve therapies and predict outcome. Recurrences of intracranial aneurysms can already be detected on 3D TOF‐MRA with a high accuracy compared to DSA with volumetric measurements being significantly more reliable than visual inspection . CFD, therefore, might not be necessary to detect those recurrences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the influence of hemodynamic forces on aneurysm initiation, growth, rupture, and recurrence after treatment can help to improve therapies and predict outcome. Recurrences of intracranial aneurysms can already be detected on 3D TOF‐MRA with a high accuracy compared to DSA with volumetric measurements being significantly more reliable than visual inspection . CFD, therefore, might not be necessary to detect those recurrences.…”
Section: Resultsmentioning
confidence: 99%
“…Recurrences between 6FU and 12FU in the cohort were identified in a previous study by the means of volumetric measurements (33 recurrences in 297 aneurysms) . As pretesting of sample geometries suggested that internal cerebral artery (ICA) geometries were subject to a high rate of nonconvergence only non‐ICA geometries were included.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, volumetric analysis of co-registered three-dimensional ToF-MRA follow-up datasets in a core laboratory, as in our study, represents an objective, rater independent method. According to Schönfeld et al , this approach leads to higher reliability compared with visual evaluation 4. Thus volume quantification based on ToF-MRA image sequences allows earlier estimation of safety and efficacy of new materials compared with studies requiring more patients to reduce the variability due to visual evaluation 2.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the quantification of small residual volumes is difficult and the sensitivity of visual evaluation of 3D ToF-MRA compared with DSA for detection of reperfusion or residual perfusion of coiled intracranial aneurysms was found to be lower for aneurysms ≤5 mm (72.2%) and ≤3 mm (63.6%) 9. However, volumetric analysis of registered 3D-ToF-MRA follow-up data sets was found to be highly sensitive and significantly more reliable than visual inspection in the detection of aneurysm recurrences 4. Allowing the detection of even smaller recurrence volumes compared to visual evaluation of 3D ToF-MRA, it presents a promising approach, though the validation against a reference standard is still missing.…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, volumetric measurement of aneurysm changes over time as an imaging end point can limit the variability of visual assessment. 13,14 On the contrary, aneurysm retreatment is the result of a completely subjective decision process involving the treating physician and the patient who always has the possibility to refuse the retreatment of the incompletely treated aneurysm. Moreover, as soon as TAR (re-treatment) is used as the primary end point of a trial, it can certainly modify the indications for retreatment for the patients included in the trial knowing that the treating physician cannot be blind regarding the treatment used.…”
Section: Pointmentioning
confidence: 99%